Application of neuro- fuzzy to component elements of a grinding wheel (2008)
The grinding wheel is made of very small sharp and hard silicon carbide abrasive particles or grits held together by strong porous bond. These silicon carbide abrasive particles are hard crystalline materials which are held together by the strong, porous bond and these abrasive materials which are of extreme hardness are used to shape other materials by a grinding or abrading action. The paper presents, an analysis of the various component elements of a typical grinding wheel using neuro- fuzzy technique. Among these component elements we have, the size of the grains and its spacing, volumetric proportion of grains, volumetric proportion of bonding material and volumetric proportion of pores. However, the work is new as it appears to be the first application of neuro- fuzzy to component elements of a grinding wheel.